THE USE OF MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING BIOLOGY - Xolboyeva Munisxon (Journals Park Publishing, 2023)
The problematic "mental attack" lesson, which plays a prominent role in teaching, and controversial (scientific discussion and free thinking) lessons are based on problematic teaching technology. The uniqueness of these lessons is based on the problematic situations that arose during the course.